Rediscovery of Clematis liboensis (Ranunculaceae) from southeastern Guizhou, China, an imperfectly known species previously known only from its type material, with a geographical extension and an amended description - Xiong, Si-Min; Liu, Ang; Jiang, Guo-Bin; Huang, Qiao-Lan; Su, Chun-Lan; Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2025)
Clematis liboensis (Ranunculaceae), an interesting and yet little known species, was discovered from Jianhe, Leishan and Rongjiang counties in southeastern Guizhou, China. This species has been previously reported only from its type locality, i.e. Libo county in southern Guizhou. Based on our careful observations of the living plants in the three populations, some important morphological characters of this species are confirmed or clarified, and an amended description is given for it. The systematic position of C. liboensis is also discussed.